Determinants of national saving in Malaysia / Raizatul Amizah Ribin@Raipin - Ribin@Raipin, Raizatul Amizah (2019)
Saving is the good way either for private or public sector. National saving in some country are very important to maintain the economic stable. This research paper aims to identify the factors that affect national saving in Malaysia. This research is taken from the year 1988 until 2018 which is 30 years as an interval time to investigate. There are used secondary data as to form the results and find it through World Development Indicators (WDI). This study determinants that can influenced the national saving, which is Gross Domestic Product, Interest rate, Dependency ratio and Export rate. The main findings are to know either all the independent variables are significant or insignificant with dependent variable. The finding show that the gross domestic product and export rate are negative significant relationship with national saving in Malaysia. But, for interest rate and dependency ratio have a positive relationship with national saving. This result will be more accurate when run the data using EVIEWS 10 SV.